Quantitative Proteome Analysis in Response to Glucose Concentration in C2C12 Myotubes - Ayano Kato; Iori Sakakibara; Taku Fukushima; Kosuke Sugiura; Tomoya Fukawa; Takeshi Nikawa; Takayuki Uchida (Applied Sciences, 2022)
Glucose is important for the maintenance of muscle function; however, it is still unclear how changes in glucose concentration affect muscle. Here, we analyzed the effect of glucose concentration on protein expression under different glucose concentration media in C2C12 myotubes. First, we performed proteome analysis in C2C12 myotubes cultured in Low (1.0 g/L), Medium (2.0 g/L), and High (4.5 g/L) glucose media. Proteome analysis revealed 113 proteins were significantly changed in group cultured in Low or Medium glucose media compared to group cultured in High glucose media. Furthermore, glycolysis, oxidative phosphorylation, and fatty acid metabolism were increased in the Medium and Low groups. Among these pathways, HK2, PFKP, NDUFA11, and FABP3 were especially upregulated proteins in Low and Medium groups. In this context, ATP production in C2C12 myotubes cultured in Low and Medium glucose media was increased. There was no significant change in myotubes morphology and myogenic differentiation factors in all groups. Finally, we examined the effect on glucose concentration in culture media on myosin isoforms expression by qRT-PCR. As a result, Myh2 and Myh4 were significantly increased in Low and Medium conditions. Altogether, Low and Medium glucose conditions induced Myh expression probably via enhancement glucose utilization.